CORPORATE GOVERNANCE, BONUS MECHANISM AND TUNNELING INCENTIVES' INFLUENCE ON TRANSFER PRICING PRACTICES - Ita Salsalina Lingga; Debbianita Debbianita; I Nyoman Agus Wijaya; Clairine Angelica Riona Saputra (LPPM STIE Muhammadiah Bandung, 2022)
This study aims to analyze the effect of” corporate governance, bonus mechanisms, and tunneling incentive “on transfer pricing.” The sample of this study consists of “manufacturing sector companies listed on the Stock Exchange” between 2015 and 2019 that have submitted a complete financial report during the observation period. The data analysis technique used is multiple linear regression. Based on the results of hypothesis testing, it can be concluded that corporate governance, bonus mechanisms, and tunneling incentives have significant effect on transfer pricing.